The JCMCTA: Glimpses from the Past - Editors, The (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7663 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):8-9